The nodal structure in the Meccan surah’s and its role in proving the existence of God - Haider Hassan Falih; Dr. Haider Taqi Fadhil Al-Allaq (Journal of College of Education, 2024)
The names and attributes of God are not the same as they are for the creatures, and what concerns us is the present and all the previous names or attributes of God, uniting them to the monotheism of God Almighty, meaning that they believe that God is the foundation of everything, but rather that He is the One in the origin of His attributes and His effectiveness, with no partner in His ownership and management. Hiding anyone is steadfast, but only He is worthy of worship and no one else, so there is no exception for Him. He emphasized that monotheism among Muslims is the basic axis of the Islamic faith, and indeed it is the axis of the entire religion. One of the greatest and most noble battles in nature and minds is the existence of the truth of God Almighty, this truth that the minds do not acknowledge despite recognizing it, and which some tongues have unjustly and arrogantly denied, so it is so clear as not Suspicions fall on him, and he is in a position beyond suspicion.